Penerapan Problem Based Learning Untuk Meningkatkan Penguasaan Konsep Sains dan Sikap Ilmiah Siswa SD - Munir Latukau (Peneliti.net, 2023)
In the current era of technology, almost all human activities require the help of sophisticated devices that can easily assist their activities. This certainly implies to educators and prospective educators to be able to apply ways of learning with the use of the latest technology. That is, educators or prospective educators must be able and understand technology in order to carry out their duties properly in accordance with the applicable curriculum. Based on the results of our research, the policy of Blended learning using Google Classroom at STKIP Kie Raha has not run optimally. This is because there is still a lack of knowledge of lecturers and students about the Blended learning model using Google Classroom. In addition, another problem is that the availability of learning information facilities at STKIP Kie Raha is not adequate. Generally, the Blended learning policy at STKIP Kie Raha still uses zoom, the collection of student assignments through WhatsApp social media. One of the solutions that can be used today by educators in changing the paradigm of teacher centered learning to student centered, namely first; Blended Learning, is a learning approach that integrates traditional face-to-face learning and distance learning using virtual resources and online learning with a variety of communication options that can be used by lecturers and students. Blended learning can be concluded that blended learning is a learning that combines or combines face-to-face learning (face to face) with ICT media, such as computers (online and offline), multimedia, virtual classes, the internet and so on.